PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP BELANJA MODAL DENGAN PERTUMBUHAN EKONOMI SEBAGAI PEMODERASI - Erdi Adyatma; Rachmawati Meita Oktaviani (Faculty of Economic and Business Universitas STIKUBANK, 2015)
The local government allocated funds in the form of capital expenditure in the local budget to increase fixed assets. During this shopping areas more used to spending relatively less productive routine. The purpose of this study is to prove empirically the effect of regional revenue and general allocation funds for capital expenditures in the District / City Central Java Province Year 2011-2013 with moderation variables Economic Growth. The population in this study is the Regency / City Central Java province which consists of 35 District / City. This study uses secondary data such as Realization Report 2011-2013 budget. In this study, the test model for hypothesis testing will be done using Moderated Regression Analysis. The data has been collected and analyzed in advance with the classic assumption test. Based on the results of this study concluded that the original income has no effect on Capital Expenditure. General Allocation Fund has a positive influence on Capital Expenditure. Directions regression coefficient is positive, meaning that an increase in the General Allocation Fund will increase capital expenditures. Economic growth does not affect the Capital Expenditure. Economic growth does not moderate relationship with the Regional Income Capital Expenditure. Economic growth does not moderate the relationship with the general allocation fund capital expenditures. Keywords: Local Revenues, General Allocation Funds, Economic Growth and Capital Expenditure